QR tag scanner / Dr. Mohd Afizi Mohd Shukran - Mohd Shukran, Dr Mohd Afizi (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Owner's identity tracking system briefcase students use QR (Quick Response) Codes developed is to create a system of safety features in a briefcase National Defence University of Malaysia (NDUM) used by students. QR code technology is the best technology to solve the problems faced by the current system. The system is capable of decode QR, information display and transmission of information through short messaging system (SMS) is the best solution to replace the current system. Results from observational studies on this new system, the implementation of QR code tag on a briefcase with QR Tag Scanner application was able to overcome the difficulties encountered in identifying the true owner of the briefcase found. However, improvements to the owner's identity tracking system briefcase stude